Can Public Providers of Health Services Procure In-house? : The Health Care Reform and Support Service Purchases Under EU Public Procurement and State Aid Law - Wahrmann, Alma (fi=Turun yliopisto|en=University of Turku|, 2018)
Following the Finnish health and social services reform public and private providers will be competing within the provision of basic health care services. The service providers compete for customers based on quality while the counties pay compensations mainly based on the amount of customers. EU state aid rules as well as the emergence of functioning markets for health services, require that there is competitive neutrality between public and private providers. Competitive neutrality may be endangered, if the public health care providers are characterised as in-house entities in accordance with public procurement law and may therefore procure support services directly from the county or the county’s other in-house entities on possibly better conditions than those available for private health service providers, procuring their services from private markets. The study aims to clarify whether the county’s direct choice service provider could procure support services, especially diagnostic services, from the county. The question is observed from the perspectives of EU law on public procurement and state aid as well as economics. The study utilises legal dogmatics, teleologic method and law and economics and strives to assess the situation under observation as versatilely and comprehensively as possible with the eclectic method. The key findings establish that while the counties’ service utility health care providers could procure services from the county based on the so called exception for own production, the counties’ corporatised health care providers would not appear to meet the Public Procurement Directive’s criteria for in-house entities. Regardless of whether the judicial form is corporatised entity or service utility of the public health service providers, they could however be characterised as undertakings in accordance with state aid law and thus advantageous in-house procurement relations could constitute state aid both when the service providers act as service utilities and companies. From an economic perspective it can be found that due to the economies of scale and requirements from specialised health care related to diagnostic services, the internal production of these services is warranted because of the need to ensure provision into health care, even though it limits competition. Irrespective of the nature of health care services, granting an advantage to public providers through procurement is not justifiable. Based on the findings of the study it is concluded that there are grounds for exploring the separation of public diagnostic services into internal services and services offered on the market, so that the corporatised public health service providers and private health service providers could also utilise these services.